Au/Pd@rGO nanocomposite decorated with poly (L-Cysteine) as a probe for simultaneous sensitive electrochemical determination of anticancer drugs, Ifosfamide and Etoposide - Hatamluyi, Behnaz; Lorestani, Farnaz; Es’haghi, Zarrin (Elsevier, 2018)
The simultaneous measurement of the concentration of anticancer drugs with a fast, sensitive and accurate method in biological samples is a challenge for better monitoring of drug therapy and better determine the pharmacokinetics. An electrochemical sensor was developed for the simultaneous determination of anticancer drugs, Ifosfamide (IFO) and Etoposide (ETO) based on pencil graphite electrode modified with Au/Pd@rGO nanocomposite decorated with poly (L-Cysteine). Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were utilized to study the properties of the modified electrode. The electrochemical behavior of IFO and ETO on the Au/Pd@rGO@p(L-Cys) modified electrode was investigated by cyclic voltammetry and differential pulse voltammetry (DPV) techniques and the obtained results confirmed its efficiency for the individual and simultaneous sensing of IFO and ETO. After optimization of electrochemical parameters, the fabricated sensor presented excellent performance in simultaneous determination of IFO and ETO with a wide linear range from 0.10 to 90.0 μM and 0.01 to 40.0 μM and low detection limits (3 Sb/m) of 9.210 nM and 0.718 nM, respectively. In addition, this study proved that the constructed sensor could be useful to simultaneous analysis of IFO and ETO in biological samples and pharmaceutical compounds.